POLIMERSILIKATNO PLASTER-REGARD, COMPRISING ORGANOKOMPOZITOV FROM PLANT MATERIAL (Municipal economy of cities (Technical science), 2013)
Proposed structure and resource-saving technology of raw meal polimersilikatnymi modifiers for arbolita based on plant-gypsum composition (RGC).